Agricultural trade interests and challenges at the WTO Ministerial Conference in Buenos Aires : A Southern Cone perspective - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This document is the result of a joint effort by the International Food Policy Research Institute (IFPRI), Group of Producing Countries from the Southern Cone (GPS), Institute for International Agricultural Negotiations Foundation (INAI), Buenos Aires Grain Exchange, International Centre for Trade and Sustainable Development (ICTSD), and Inter-American Institute for Cooperation on Agriculture (IICA). Chapters 2 and 8 of this book were undertaken as part of, and funded by, the CGIAR Research Program on Policies, Institutions, and Markets (PIM), led by the International Food Policy Research Institute (IFPRI). The opinions expressed herein belong to the authors and do not necessarily reflect those of PIM, IFPRI, or the CGIAR. The content of the individual papers is the responsibility of the authors, and therefore the analysis, conclusions, and recommendations presented herein should not be attributed to IFPRI, GPS, IICA, INAI, ICTSD, or Bolsa de Cereales.